Nitrogen, phosphorus and sulfur co-doped ultrathin carbon nanosheets as a metal-free catalyst for selective oxidation of aromatic alkanes and the oxygen reduction reaction. Issue 47 (17th November 2016) - Zhu, Ya-Nan; Cao, Chang-Yan; Jiang, Wen-Jie; Yang, Shu-Liang; Hu, Jin-Song; Song, Wei-Guo; Wan, Li-Jun
Abstract : Nitrogen, phosphorus and sulfur co-doped ultrathin carbon nanosheets showed outstanding activity for selective oxidation and oxygen reduction reaction. Abstract : Carbon materials have attracted considerable interest as metal-free heterogeneous catalysts owing to their superior physicochemical properties, including low cost, stability, and easily tailorable structures as well as excellent catalytic activity. In this study, we have designed an efficient method to produce ultrathin carbon nanosheets (∼2.2 nm) with multi-heteroatom (nitrogen, phosphorus and sulfur) doping and a high surface area (up to 1198 m 2 g −1 ). This method employs poly(cyclotriphosphazene- co -4, 4′-sulfonyldiphenol) (PZS) as the main carbon source and N, P, S-doping sources, while g-C3 N4 nanosheets act as the morphology template, extra N doping source and porogen. The doped carbon nanosheets are an excellent metal-free carbocatalyst for selective oxidation of aromatic alkanes in aqueous solution and electrochemical catalyst for the oxygen reduction reaction in an alkaline medium.